A Case of William's Syndrome in a Ugandan Child: A Feasible Diagnosis Even in a Low-Resource Setting - Massimo Mapelli; Paola Zagni; Valeria Calbi; Aliku Twalib; Roberto Ferrara; Piergiuseppe Agostoni (MDPI AG, 2021)
Background: Williams-Beuren syndrome (WS) is a rare, complex, congenital developmental disorder including cardiovascular manifestations, intellectual disability and a peculiar cognitive and behavior profile. Supravalvular aortic stenosis (SVAS) is the most frequent cardiovascular abnormality in WS children. Data on WS patients in sub-Saharan Africa are scarce. A genetic study is usually required for a definite diagnosis, but genetic testing is often unavailable in developing countries and the combination of a typical clinical phenotype and echocardiographic profile helps to confirm the diagnosis. Case Report: We report the case of a 5-year-old Ugandan child admitted to a large no profit hospital after he was initially managed as a case of infective endocarditis. A physical examination revealed the typical features of WS. A cardiac echo showed severe SVAS (peak gradient 80 mmHg) with a normal anatomy and function of the aortic valve and mild valvular pulmonary stenosis. The child also had a moderate intellectual disability and a characteristic facies consistent with WS. Conclusion: We present the first reported case of WS in Uganda. Cardiac echo and a characteristic clinical picture could be enough to exclude more common causes of heart failure (i.e., rheumatic heart disease) and to make the diagnosis even when specific genetic tests are not available.